DETERMINING FACTORS OF ISLAMIC BANK CAPITAL STRUCTURE IN INDONESIA - Anggraeni, Anita Meliana; Zuhroh, Idah; Suliswanto, Muhammad Sri Wahyudi (Program Studi Ekonomi Pembangunan, 2021)
In the capital structure there are several determinants to determine the capital structure, these determinants will later be used as a consideration in determining the capital structure. This research will analyze the factors that determine the capital structure of Islamic banks in Indonesia. The data used for this research are in the period 2015.1-2019.4. The data used is data from the Indonesian Islamic Commercial Bank. For analysis data processing using panel data regression with the best model selection. The data variable consists of 2 variables, namely dependent and independent. The dependent variable in this study is the Capital Adequacy Ratio (CAR). While the independent variables in this study are Return On Assets (ROA), Return On Equity (ROE), Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR). From the results of the analysis for this study, it is known that the Return On Assets (ROA) variable has a positive and significant effect on the Capital Adequacy Ratio (CAR) variable. For variables that have a negative and significant effect on the CAR variable are the Return On Equity (ROE) and Non-Perfoming Financing (NPF) variables. Whereas the Financing to Deposit Ratio (FDR) variable has a positive and insignificant effect on Capital Adequacy Ratio (CAR) variable.